2006
DOI: 10.1002/pds.1207
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of NSAIDs withdrawn from the market due to hepatotoxicity: lessons learned from the bromfenac experience

Abstract: Drug-induced hepatotoxicity is the leading cause of acute liver failure (ALF) in the US and the most common adverse event causing drug non-approval and drug withdrawal by the U.S. Food and Drug Administration (FDA). Three different nonsteroidal anti-inflammatory drugs (NSAIDs) have been withdrawn in the UK and/or the US due to hepatotoxicity (bromfenac, ibufenac, and benoxaprofen). A systematic review of clinical trials data for these drugs was performed in an effort to identify possible early signals that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 11 publications
(9 reference statements)
0
73
0
4
Order By: Relevance
“…91,92 Several NSAIDs, such as oral bromfenac and lumiracoxib, were withdrawn or never approved in the United States because of hepatotoxicity concerns. 92,93 The mechanism for liver injury is not clearly known, although it appears to be immunologically mediated and idiosyncratic. NSAIDs and strategies for prevention of side effects; however, the recommendations vary.…”
mentioning
confidence: 99%
“…91,92 Several NSAIDs, such as oral bromfenac and lumiracoxib, were withdrawn or never approved in the United States because of hepatotoxicity concerns. 92,93 The mechanism for liver injury is not clearly known, although it appears to be immunologically mediated and idiosyncratic. NSAIDs and strategies for prevention of side effects; however, the recommendations vary.…”
mentioning
confidence: 99%
“…Goldkind and Laine (29) suggested that ALT elevations alone do not reliably signal serious hepatotoxicity, elevated ALT and AST may be predictors of an increased risk of acute liver failure. Page (8) reported the simultaneously decreasing of protrombin time with increasing hepatic transaminase (AST, ALT), LDH and bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This species was shown to be severely hepatotoxic for mice (Hawkins et al, 1985). Note: Drugs like troglitazone, bromfenac, ticrynafen, benoxaprofen, trovafloxacin, ebrotidine, nimesulide, nefazodone, ximelagatran and pemoline have been withdrawn due to hepatotoxicity (Xu et al, 2004;Smith et al, 2005;Goldkind & Laine, 2006).…”
Section: Water Causing Hepatotoxicitymentioning
confidence: 99%